Interannual oscillations in winter rainfall over Europe: Iberia study case - Gomes,Pedro Tildes (2011)
Low-frequency variability is a good starting point for modelling the climate system and understanding mechanisms that can give us some indication of future climate evolution. This work aims to better understand the degree of association between the atmospheric circulation and precipitation over Europe and the Iberian Peninsula. To achieve this goal, the standard precipitation anomalies in Europe and the anomalies of sea level pressure (SLP) in the North Atlantic region during the twentieth century were subjected to Multi-Channel singular spectrum analysis (MSSA). This procedure allows us to measure the degree of association between the SLP and precipitation fields. The identification of common oscillations between the two climatic fields led not only to the confirmation of the physical meaning of these oscillations, but also to the identification of the dynamical evolution of the ocean-atmosphere system in the North Atlantic. Two oscillations, statistically significant, common to both the precipitation field and SLP field were isolated with periods of about 8 years and 5.3 years. The 8-year oscillation is the most significant and robust of the two climatic fields and exhibits a classic NAO pattern, with an out-of-phase variability between northern and southern parts of the domain. Furthermore, it is characterized by a westward propagation of the climate signal and a perfect out-of-phase variability between the precipitation and SLP. The 8-year oscillation is also very significant in the Iberian Peninsula and is associated with dry winters and wet winters, whose sequence was identified for the twentieth century. The 5.3-year oscillation is related to the East Atlantic Pattern that exhibits another dipolar structure, with an out-of-phase variability between southwest and northwest Europe. The regularity of the 8 year oscillation can be anticipated with a degree of certainty, thus permitting a prediction of the occurrence of wet and dry years and allowing for a better management of water resources